Exploration of upstream and downstream process for microwave assisted sustainable biodiesel production from microalgae Chlorella vulgaris. (September 2016) - Sharma, Amit Kumar; Sahoo, Pradeepta Kumar; Singhal, Shailey; Joshi, Girdhar
Highlights: Upstream and downstream process in Chlorella vulgaris has been explored for microwave assisted sustainable biodiesel production. 92.53% harvesting efficiency was achieved by a combined method of flocculation and filtration. 84.03% yield obtained by acid-based catalyzed transesterification in microwave assisted reactor. Microwave assisted transesterification was more efficient than conventional heating transesterification. Chlorella vulgaris can produce 13.62 ton/hectare/year biodiesel. Abstract: The present study explores the integrated approach for the sustainable production of biodiesel from Chlorella vulgaris microalgae. The microalgae were cultivated in 10 m 2 open raceway pond at semi-continuous mode with optimum volumetric and areal production of 28.105 kg/L/y and 71.51 t/h/y, respectively. Alum was used as flocculent for harvesting the microalgae and optimized at different pH. Lipid was extracted using chloroform: methanol (2:1) and having 12.39% of FFA. Effect of various reaction conditions such as effect of catalyst, methanol:lipid ratio, reaction temperature and time on biodiesel yields were studied under microwave irradiation; and 84.01% of biodiesel yield was obtained under optimized reaction conditions. A comparison was also made between the biodiesel productions under conventional heating and microwave irradiation. The synthesized biodiesel was characterized by 1 H NMR, 13 C NMR, FTIR and GC; however, fuel properties of biodiesel were also studied using specified test methods as per ASTM and EN standards.